Object Lessons. - Hoffmann, Leah (Communications of the ACM, 2015)
An interview is presented with computer scientist Bertrand Meyer. He discusses the creation and development of the Eiffel computer programming language and environment. Other topics include his faculty position at Eidgenössische Technische Hochschule (ETH) Zurich in Switzerland, the massive open online course (MOOC) on computer programming he helped design, and the Agile approach to software development.